Game Online Hack (Literature Review): The Impact of Online Games on the Physical Fitness of Students Aged 13-17 Years - Dos Santos, Hezron Alhim; Dos Santos, Maria Herlinda; Arisman, Arisman; Endang Pratiwi; Ilahi, Rahmat (Universitas PGRI Palembang, 2022)
The advancement of technology has significantly impacted teenagers' lifestyles, particularly in terms of physical activity and fitness. One notable phenomenon is the increasing number of students aged 13-17 who spend hours playing online games. This study aims to review the impact of online gaming on teenagers' physical fitness based on various existing studies. Using a literature review method, this article examines research findings related to decreased physical activity, increased risk of obesity, and the psychological and social effects associated with online gaming habits.